2006
DOI: 10.1017/s1474745606002965
|View full text |Cite
|
Sign up to set email alerts
|

The Internet, cross-border trade in services, and the GATS: lessons from US–Gambling

Abstract: The rapid development of the Internet has led to a growing electronic cross-border delivery of services. While the WTO negotiations have not caught up to the reality of such service trade, the first GATS case dealing with the Internet, namely ' United States -Measures Affecting the Cross-Border Supply of Gambling and Betting Services ', has advanced matters. This paper distils the substantive conclusions of the case and remaining questions in relation to Internet-supplied services and certain core concepts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…On the surface, gambling and health may seem to have little in common, but the decision has important implications for telemedicine. The ruling confirmed that the GATS applies to services provided electronically across borders, and that prohibiting the electronic provision of such a service is not compatible with commitments made under mode 1 (the part of the agreement which would cover telemedicine) [11].…”
Section: Resultsmentioning
confidence: 99%
“…On the surface, gambling and health may seem to have little in common, but the decision has important implications for telemedicine. The ruling confirmed that the GATS applies to services provided electronically across borders, and that prohibiting the electronic provision of such a service is not compatible with commitments made under mode 1 (the part of the agreement which would cover telemedicine) [11].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, although the GATS states nothing explicitly about information flows, WTO members have begun to apply these obligations when settling disputes about cross-border information flows (Wunsch-Vincent 2006;Goldsmith and Wu 2006). The WTO's Dispute Settlement Body has adjudicated two trade disputes related to information flows.…”
Section: Why Have Governments Used Trade Agreements To Regulate Informentioning
confidence: 99%
“…The Bush Administration pushed through several free trade agreements with language on e-commerce. The FTAs with Chile, Singapore, Peru, Columbia, and CAFTA-DR stated that signatories should avoid erecting new trade barriers to digital trade as well as saying that neither party may include local presence requirements (Wunsch-Vincent, 2003: 32–34). However, none of these agreements contained language on the free flow of information or clarified when nations could restrict the flow.…”
Section: The Free Flow Of Information As a Trade Issue: The 1960s–2001mentioning
confidence: 99%